Subjects with allergic reactions to drugs show in vivo polarized patterns of cytokine expression depending on the chronology of the clinical reaction - Posadas, Sinforiano Jose; Leyva-Fernández, Laura; Torres-Jaén, María Josefa; Rodríguez-Bada, José Luis; Bravo, Inmaculada; Rosal, Manuel; Fernández, Javier; Juárez, Carlos; Blanca, Miguel (Elsevier, 2000)
Background: The mechanisms involved in adverse drug reactions with an immunologic basis (ADRIB) can be antibody dependent, mainly IgE or T cell dependent (sensitized T cells). These mechanisms are regulated by a number of cytokines, including IL-2, IL-4, IL-5, IFN-γ, and TNF-α, which follow the classical TH1/TH2 immunologic paradigm. Although evidence for this has been seen in ex vivo studies, the results are heterogeneous, and few in vivo studies have been carried out in subjects with ADRIB. Objective: We studied a group of patients who experienced either immediate reactions (n = 10) or nonimmediate reactions (n = 9) to drugs to determine the cytokine pattern profile during the acute stage of the response, as well as after recovery. Methods: PBMCs were taken at different time intervals of 24 hours or less and 7, 15, and 30 days after the onset of the reaction, and the specific cytokine transcription and production were determined by using quantitative competitive RT-PCR and ELISA, respectively. Results: There was a transient polarized pattern corresponding to a TH1 response with IL-2, IFN-γ, and TNF-α in nonimmediate reactions and to a TH2 response with IL-4 in immediate reactions. Conclusions: This is the first in vivo demonstration of these TH1/TH2 patterns in subjects with ADRIB and confirms that çan immunologic process is occurring related to the mechanisms involved in the pathologic manifestation. These findings are relevant to the understanding of the pathophysiologic mechanisms involved in ADRIB, suggesting that further studies in this direction are warranted.
Manuscrito aceptado el 28 junio de 2000
Keywords: Alergia; Allergy; TH1; TH2; Drug reactions; Cytokines